2013
DOI: 10.1097/olq.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Epidemiological Typing of Penicillinase-Producing Neisseria gonorrhoeae and Their blaTEM-135 Gene Variants in Nanjing, China

Abstract: A high prevalence of PPNG and blaTEM-135 was found in Nanjing, China. bla(TEM-135) might be a precursor in the evolution into an extended-spectrum β-lactamase that can degrade ceftriaxone, which stresses the need to continuously monitor PPNG, blaTEM-135, and additional evolving blaTEM gene variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…Only one K. pneumoniae harbored a TEM-ESBL (TEM-135) subtype, which has also been reported in other parts of China. 43 As reported in other previous works, the OXA-1 subtypes were co-harbored along with other enzymes. 10 Statistical evaluation of our data revealed that bla TEM and bla CTX-M-1 group genes were positively associated with resistance to more than three β-lactams.…”
Section: Discussionsupporting
confidence: 66%
“…Only one K. pneumoniae harbored a TEM-ESBL (TEM-135) subtype, which has also been reported in other parts of China. 43 As reported in other previous works, the OXA-1 subtypes were co-harbored along with other enzymes. 10 Statistical evaluation of our data revealed that bla TEM and bla CTX-M-1 group genes were positively associated with resistance to more than three β-lactams.…”
Section: Discussionsupporting
confidence: 66%
“…No extended-spectrum ␤-lactamase (ESBL) has yet been acquired or developed in gonococci. Nevertheless, in many currently circulating strains, the bla TEM-135 gene, which differs by one single nucleotide polymorphism (SNP) from bla TEM-1 , has been found, and only one additional SNP could result in an ESBL capable of hydrolyzing and degrading ESCs (183)(184)(185).…”
Section: Penicillin Resistancementioning
confidence: 99%
“…These studies also highlighted that bla TEM-135 may occur in distinct genetic backgrounds and suggested that the gene has continued to be shared among gonococci via horizontal genetic exchange, having been found on the Asian and Rio/Toronto plasmid types and across various multilocus sequence types (MLST) and N. gonorrhoeae multiantigen sequence types (NG-MAST) (8,11,12,14).…”
mentioning
confidence: 99%
“…Data on the rate at which penicillinase-producing N. gonorrhoeae (PPNG) isolates carry the bla TEM-135 gene are limited, ranging from 9.4% (9/96 PPNG isolates) in Thailand (9) and 20% (2/10 PPNG isolates) in Japan (12) to 58% (66/114 PPNG isolates) in China (11). These studies also highlighted that bla TEM-135 may occur in distinct genetic backgrounds and suggested that the gene has continued to be shared among gonococci via horizontal genetic exchange, having been found on the Asian and Rio/Toronto plasmid types and across various multilocus sequence types (MLST) and N. gonorrhoeae multiantigen sequence types (NG-MAST) (8,11,12,14).…”
mentioning
confidence: 99%